2019
DOI: 10.1016/j.compstruct.2019.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Compressive failure of woven fabric reinforced thermoplastic composites with an open-hole: An experimental and numerical study

Abstract: This research presents a detailed experimental and numerical study on the compressive failure of woven fabric reinforced thermoplastic composites, with an open-hole and with a pinned open-hole. The experimental evaluations are performed on the composite specimens using the Combined Loading Compression (CLC) evaluation method. Experimental results, including load response and damage morphology, are obtained and analysed. A meso-scale damage model is developed, based on Continuum-Damage-Mechanics (CDM), for pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…is the characteristic length, which can be determined based on the volume of the elements. For more details of the characteristic length calculation, please refer to [6,[14][15][16].…”
Section: Intralaminar Damage Initiationmentioning
confidence: 99%
“…is the characteristic length, which can be determined based on the volume of the elements. For more details of the characteristic length calculation, please refer to [6,[14][15][16].…”
Section: Intralaminar Damage Initiationmentioning
confidence: 99%
“…To calculate and compare the values of the contact pressures caused by the soft-gelatine projectiles and hard aluminium-alloy projectiles, the impact behaviour of the CF/PEEK composite target was modelled. The relevant material properties of the CF/PEEK composites required for the modelling studies may be found from the literature [11,12,15,[48][49][50][51][52][53][54] and are given in Table 4.…”
Section: Modelling Studiesmentioning
confidence: 99%
“…It can be seen that the aluminum-alloy impacted CF/PEEK composite exhibited a significantly higher reaction force than the gelatineimpacted CF/PEEK composite. The maximum reaction forces associated with the soft-gelatine Table 4 The input parameters for the composite damage model [11,12,15 Fig. 15 The FE model for simulating (a) the soft-gelatine particle (PC3D) impact and (b) the hard aluminiumalloy projectile impact on the composites and the hard aluminium-alloy impacts on the CF/PEEK composites were calculated to be 4.4 kN and 7.4 kN, respectively, see Fig.…”
Section: Modelling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The J-integral value was calculated using the strain values and the fracture energy value was finally obtained according to some assumptions. Many studies have been performed [12][13][14][15][16][17][18][19][20][21] on the failure behavior of an open-hole composite laminate. However, studies regarding the validity assessment of the suggested PFA by comparing it to the values obtained from experimental studies are scarce.…”
Section: Introductionmentioning
confidence: 99%